Inherited Causes of Exocrine Pancreatic Dysfunction - Peter R Durie (Canadian Journal of Gastroenterology)
The exocrine pancreas is functionally immature at birth. Protease function is probably adequate, but lipase activity approximates 5% to 10% of adult values in the newborn and remains low in infancy. Pancreatic amylase secretion is essentially absent at birth and remains low through the first years of life. Functional disturbances of the exocrine pancreas are less frequent in childhood than in adult life. Causes of pancreatic dysfunction in childhood can be divided in two general categories: hereditary conditions, which directly affect the pancreas; and acquired disorders, in which loss of pancreatic function is a secondary phenomenon. Most inherited causes of pancreatic dysfunction are due to a generalized disorder. Cystic fibrosis is, by far, the most common inherited cause of disturbed pancreatic function among Caucasian children. All other inherited causes of exocrine pancreatic dysfunction (eg, Johanson-Blizzard syndrome) are uncommon or rare.